Age Diversity Management and Bridging Generational Gaps for Organizational Productivity: A Theoretical Study (Orchid Insights: A Multidisciplinary Journal of Orchid College, 2025)
In today’s increasingly age-diverse workforce, organizations are encountering both challenges and opportunities in managing generational differences. This study investigates the impact of age diversity management on organizational productivity, focusing on strategies that bridge generational gaps between Baby Boomers, Generation X, Millennials, and Generation Z. Through a comprehensive review of literature and empirical analysis, this research explores how effective age diversity management contributes to employee engagement, collaboration, and overall productivity. It highlights the importance of fostering an inclusive work environment that values the unique strengths of each generation. The study further discusses the role of leadership in facilitating cross-generational collaboration and the potential for innovation through diverse perspectives. By addressing generational differences and promoting inclusivity, organizations can harness the potential of a multi-generational workforce to enhance productivity and drive sustainable growth. The findings provide practical insights for HR professionals and organizational leaders aiming to optimize workforce diversity for competitive advantage.